State Dependence in Unemployment - Ahmad, Nisar (International Journal of Economics and Financial Issues, 2013)
This study examines the extent state dependence among unemployed immigrants in a dynamic discrete choice framework. Three alternative methodologies are employed to control for the problem of the initial condition. The empirical findings show that there is a considerable correlation between the unobserved individual heterogeneity and the initial condition and that the degree of state dependence is overstated if we do not address this problem. The results show that an individual who was unemployed at period “t-1” has 6.5 percentage points higher probability of being unemployed again at period t compared to an individual who was employed at period “t-1”. Keywords: Immigrants; unemployment; state dependence; unobserved heterogeneity; dynamic random effects models. JEL Classifications: C23; C25; J22